An Ethnoarchaeological Model for the Identification of Prehistoric Tepee Remains in the Boreal Forest - Janes, Robert R. (ARCTIC, 1989)
The deliberate observation of contemporary northern hunters is one way of enhancing the interpretation of the archaeological record in the western Canadian Subarctic. The paper is based on six months of archaeological ethnography at a residential hunting camp in the mid-Mackenzie Valley, Northwest Territories, Canada, followed by archaeological excavations at the same camp of Dene hunters. The conceptual framework of this research is ethnoarchaeology, which encompasses the theoretical and methodological aspects of a comparing ethnographic and archaeological data. A model for identifying teepee remains in the absence of surficial architectural remains is presented, based on the excavation of a currently occupied tepee at the hunting camp. This model consists of a number of attributes, ranging from a central hearth to subterranean storage facilities. The probability that tepee architecture is present increases with every attribute that can be documented archaeologically. The presence or absence of architectural remains is essential in the identification of site function, and site function is the key to reconstructing the regional settlement pattern in pre-ethnographic times. There is a certain urgency in integrating first-hand accounts of northern hunters with the archaeological record, as opportunities to do so continue to dwindle with the passage of time and the ever-increasing pace of culture change in the western Canadian Subarctic.Key words: ethnoarchaeology, archaeology, ethnography, archaeological methodology, Northern Athapaskan, Dene, Mackenzie Valley, Subarctic Mots clés: ethnoarchéologie, archéologie, enthnographie, méthodologie archéologique, Athapaskan septentrional, Déné, vallée du Mackenzie, subarctique